The Dynamics of Power in Labor Markets: Monopolistic Unions versus Monopsonistic Employers - Samuel Dodini; Kjell G. Salvanes; Alexander Willén (Institute of Labor Economics (IZA), 2022)
This paper brings together the modern research on employer power and employee power by empirically examining the effects of unionization on worker earnings, employment, and inequality across differently concentrated markets. Exploiting national tax reforms to union membership dues as exogenous shocks to unionization, we show that high levels of unionization mitigate the negative wage and employment effects generated by imperfect competition. We also identify considerable effect heterogeneity with respect to worker types across differentially concentrated markets, and show that this has major implications for the role of unions in shaping labor market wage inequality.
Keywords: J23; J24; J42; J51; J52; J63; 330; monopsony; skills; unions; market concentration